Complex synergistic amino acid–nucleotide interactions contribute to the specificity of NagC operator recognition and induction. Issue 7 (20th May 2019) - Fernandez, Marion; Plumbridge, Jacqueline
Abstract : NagC is a transcription factor that represses genes involved in N -acetylglucosamine catabolism in Escherichia coli . Repression by NagC is relieved by interaction with GlcNAc6P, the product of transport of GlcNAc into the cell. The DNA-binding domain of NagC contains a classic helix–turn–helix (HTH) motif, but specific operator recognition requires, in addition, an adjacent linker sequence, which is thought to form an extended wing. Sequences in the linker region are required to distinguish NagC-binding sites from those of its paralogue, Mlc. In investigating the contribution of the HTH to operator recognition, we have identified mutations in the first two positions of the recognition helix of the DNA-binding motif of NagC, which change NagC from being a repressor, which binds in the absence of the inducing signal (GlcNAc6P), to one whose binding is enhanced by GlcNAc6P. In this case GlcNAc6P behaves as a co-repressor rather than an inducer for NagC. The NagC mutants exhibiting this paradoxical behaviour have basic amino acids, arginine or lysine, at two critical positions of the recognition helix. Introducing a third amino acid change converts NagC back to a protein, which represses in the absence of GlcNAc6P. The triple mutant also effectively represses a modified NagC operator that is not repressed by wild-type NagC, showing that this form of NagC is a more promiscuous DNA binder. Specific recognition of the NagC operator thus involves a modulation of basic amino acid–DNA interactions, which affects the ability to discriminate against other permissive sites.